Pemanfaatan Limbah Kotoran Ayam Dan Sapi Menjadi Biogas Sebagai Sumber Energi Alternatif Rumah Tangga - syah, zulfadri; Hairuddin, Miftah Chairani; Adiningsih, Ridhayani; Akbar, Fajar (Jurnal Kesehatan Lingkungan Mapaccing, 2024)
The droppings produced by chickens and cows cause odors that can harm the health of people around the cage, especially the psychosomatic symptoms that people complain about. The odor emitted comes from the nitrogen and sulfide elements in chicken droppings, which during the decomposition process will form ammonia, nitrite and hydrogen sulfide gas. Gas can come from various kinds of organic waste, animal waste can be used for energy through the process of anaerobic digestion. The research method used was experimental research. This biogas research produces biogas from a mixture of chicken and cow manure with a ratio of 3:1, namely 3 kg of chicken manure and 1 kg of cow manure and water as a diluent. The fermentation process in biogas lasts for 17 days and monitoring is carried out regarding the development of methane gas production in the digester and temperature measurements are carried out every day. Based on the data and results of measurements of the temperature and quality of the gas produced, it was found that the average temperature in the digester was in mesophilic conditions at a temperature of 24 – 32 ˚C. This temperature is considered optimal so that it produces good quality methane gas The conclusion of this research is that chicken and cow manure waste can produce good methane gas and produce a blue flame with a flame duration of 11 seconds. Suggestions for researchers are to use a larger digester and use more waste so that more methane gas is produced.